Special delivery: A hardwood‐killing bark beetle vectors its unusual symbiote among host trees - Debra L. Wertman; Richard C. Hamelin; Allan L. Carroll (Ecosphere)
Abstract In mutualistic symbioses with fungi, herbivorous insects such as bark beetles (Coleoptera: Curculionidae: Scolytinae) gain access to resources that are unavailable in the absence of fungal mutualists, while fungi benefit from insect‐vectored dispersal. The most well‐studied mutualists of tree‐killing bark beetles in conifer systems are certain ophiostomatoid fungi (Ascomycota: Ophiostomatales and Microascales) that benefit beetles through their nutritional and phytopathogenic activities. The alder bark beetle, Alniphagus aspericollis, is a hardwood‐infesting bark beetle living with a non‐ophiostomatoid associate, Neonectria bordenii, in its red alder, Alnus rubra, host. We evaluated the hypothesis that the alder bark beetle–N. bordenii association represents a symbiosis similar to tree‐killing bark beetle–ophiostomatoid mutualisms in conifer systems by assessing the tree‐killing ability of the alder bark beetle and testing the prediction that the beetle vectors the fungus among host trees. We tested this prediction according to Leach's postulates for an insect vector of a plant‐associated microbe. Emergent alder bark beetles were collected across three dispersal flights and five locations throughout southwestern British Columbia, Canada, in a single season, and assessed for presence/absence of N. bordenii by quantitative PCR (qPCR) and culturing. Phloem samples (beetle‐attacked and not attacked) collected from bolts from a laboratory transmission experiment and trees in situ were also analyzed by qPCR for presence/absence of N. bordenii. The alder bark beetle attacked apparently healthy red alders across sites and was determined to have caused mortality of 86% of colonized trees. N. bordenii was detected in 98% (n = 214/218) of individual beetles by qPCR, and viable N. bordenii was recovered from 46% (n = 103/223) of beetles by culturing. qPCR analysis of phloem samples originating from a transmission experiment and trees attacked under natural conditions revealed that alder bark beetles introduce N. bordenii into phloem from healthy red alders (laboratory transmission rate = 42%). Our results indicate that the alder bark beetle vectors N. bordenii among host red alders and that the association between these two organisms is thus symbiotic. The consistent presence of N. bordenii across samples and locations suggests that this symbiosis may represent a unique bark beetle–fungus mutualism in red alder.